Media and Drugs - Ivanović, Miroslav (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
The relationship between media and drugs is discussed in this article from the point of view of the possible influence of the media on drug abuse. The impact of the media on some types of crime, such as violent crime, is dubious, while it is proven in the case of drug abuse (tobacco, alcohol). The influence of the media is accomplished through a variety of forms: news, advertising, entertainment shows, art production, and so on. It is shown that the effect of advertising and news on drug abuse is easy to measure, while this is not the case with artistic production and entertainment. We emphasise the importance of this problem for any strategy of prevention of drug abuse.